A comparative study of Pleurosigma subrectum and P. acus (Bacillariophyta) - Sterrenburg, Frithjof A.s.; Stidolph, Stuart R.; Sar, Eugenia A.; Sunesen, Ines (Phytotaxa, 2015)
In continuation of an earlier paper on Pleurosigma species with an (almost) non-sigmoid valve and raphe sternum, a comparative study was made in LM and SEM of Pleurosigma subrectum and P. acus. For P. subrectum, slides and a subsample of the type material were examined. For P. acus no unmounted material permitting SEM investigation is extant; a sample containing specimens fully matching the type in LM was therefore used as epitype material for SEM. The original data on striation of P. acus are emended. No morphological differences indicating separate specific status of these two taxa were observed and P. acus is therefore here designated a heterotypic synonym of P. subrectum. From the data now available, this is a very widely distributed species. The study demonstrates the indispensable role of collections for investigations on the diversity and distribution of diatom species.